2020
DOI: 10.1177/0961203320952864
|View full text |Cite
|
Sign up to set email alerts
|

Trends in mortality from lupus in Spain from 1980 to 2018

Abstract: Background Recent studies suggest that Systemic lupus erythematosus (SLE) mortality rates in Spain are decreasing. However, SLE mortality in Spain has been poorly studied. The purpose of study is to assess the temporal trends of mortality rates in the Spanish population with SLE from 1980 to 2018. Methods Death records and mid-year population data were collected from the National Statistics Institute. Age-standardized mortality rates were calculated for overall population and for each sex and age group. Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Bartels et al 22 demonstrated 10-year mortality rate of 26% in SLE compared with 19% for age-matched comparators (hazards ratio [HR], 2.1; p < 0.01) and increased HR of CVD event or death (HR, 1.8; p = 0.01). This finding was further supported by the recently published article by Hernandez-Rodriguez et al, 23 which examined death records and mid-year population in Spain from 1980 to 2018. They also found the overall SLE mortality rates increased in Spain from 0.83 per 1,000,000 in 1980 to 1984 compared with 1.77 per 1,000,000 from 2014 to 2018.…”
Section: Discussionsupporting
confidence: 62%
“…Bartels et al 22 demonstrated 10-year mortality rate of 26% in SLE compared with 19% for age-matched comparators (hazards ratio [HR], 2.1; p < 0.01) and increased HR of CVD event or death (HR, 1.8; p = 0.01). This finding was further supported by the recently published article by Hernandez-Rodriguez et al, 23 which examined death records and mid-year population in Spain from 1980 to 2018. They also found the overall SLE mortality rates increased in Spain from 0.83 per 1,000,000 in 1980 to 1984 compared with 1.77 per 1,000,000 from 2014 to 2018.…”
Section: Discussionsupporting
confidence: 62%
“…The number of participants was small and, consequently, the more under-represented opinions may have been overlooked, without achieving sufficient significance to be identified. However, there is no agreement on the panel size for Delphi studies and panels with “small” size also provide reliable criteria when they include highly trained experts (Akins et al ., 2005; Keeney et al ., 2001). Nevertheless, expert participants came from across Spain, from different settings and services, which conferred high representativeness.…”
Section: Limitationsmentioning
confidence: 99%
“…In Spain, SLE is one of the most frequent autoimmune diseases, with a prevalence of 210/100,000 inhabitants (Cortés Verdú et al, 2020;Seoane-Mato et al, 2018). Prognosis of SLE has significantly improved recently (Hernández-Rodríguez et al, 2020); however, people with SLE have a mortality risk two to three times higher than the general population (Bernatsky et al, 2006). Prompt diagnosis, accurate treatment, and close follow-up are key to prevent rapid disease progression and minimize the accumulation of organ damage (Mcelhone et al, 2006) and survival (Bernatsky et al, 2006;Bruce et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…9 Previous epidemiological studies with standardised methodologies have examined the SLE mortality rates in Spain over large periods of time. 10,11 These studies showed that overall age-standardised mortality rates (ASMRs) due to SLE increased from 1980 to 1999 and remained stable until 2018.…”
Section: Introductionmentioning
confidence: 99%